Political Science and Digitalization - Global Perspectives - Kneuer, Marianne; Milner, Helen V. (Verlag Barbara Budrich, 2019)
Digitalization is not only a new research subject for political science, but a transformative force for the discipline in terms of teaching and learning as well as research methods and publishing. This volume provides the first account of the influence of digitalization on the discipline of political science including contributions from 20 different countries. It presents a regional stocktaking of the challenges and opportunities of digitalization in most world regions.